Kan die Swartman 'n sukses van besigheid maak? 'n Empiriese beskouing van die opleidingsbehoeftes van swart algemene handelaars in Lebowa - Nico J. Smith (South African Journal of Business Management, 1983)
– Can the Black man make a success of business? An empirical analysis of the managerial problems of black dealers in Lebowa The success rate with training black entrepreneurs leaves much room for improvement. In this article the problems with training Blacks in general are discussed. The conclusion is that training needs are not correctly identified, and tutors are not always sufficiently educated and motivated. By means of research done in Lebowa, it is indicated which aspects should receive more attention when training the black businessman. The following aspects were researched specifically to identify the needs: background problems such as cultural aspects and overpopulation; location and problems with shop design layout and atmosphere; the organizational structure and personnel management. Limited knowledge of personnel needs and the absence of good delegation of authority are identified as important problems; purchasing management, the typical buyer and purchasing problems are identified; marketing management with special reference to pricing and promotion, and financial management were also investigated and the findings are that the security problem and the weak record keeping of respondents limits them in exercising sound financial management. On the basis of this information, guidelines for a training programme are proposed in conclusion.
Keywords: 650